Ramsay hunt syndrome (herpes zoster oticus) - S Karthiga Kannan; J Eugenia Sherubin; S Sajesh; K P Gopakumar (Wolters Kluwer Medknow Publications, 2012)
Ramsay Hunt syndrome (RHS) is defined as an acute peripheral facial neuropathy caused by the reactivated latent varicella zoster virus (VZV) in the geniculate ganglion; characterized with erythematous vesicular rash of the skin of the ear canal, auricle, facial skin, oral mucosa and facial palsy (also known as herpes zoster oticus). This article reports a case of Ramsay Hunt Syndrome (RHS) in a 37-year-old male patient depicting the classical signs.